Teaching Basketball to School-Aged Students: A Systematic Analysis of Instructional Methods in Physical Education - Edhu Wigraha, Sheva; Arif Al Ardha, Muchamad; Sawa Bikalawan, Sauqi; Mark Arbaan, Jay (Proceeding of International Joint Conference on UNESA, 2025)
This systematic review examines the instructional strategies applied in teaching basketball to school-aged children within Indonesian physical education (PE) settings. Although traditional methods centered on repetitive drills remain widespread, they often fall short in promoting comprehensive understanding and active student participation. In contrast, contemporary approaches such as Teaching Games for Understanding (TGfU) and Sport Education (SE) prioritize tactical awareness, decision-making, and student engagement, aligning with Indonesia’s educational emphasis on Higher-Order Thinking Skills (HOTS). By reviewing ten highly cited SCOPUS-indexed studies published between 2020 and 2025, this study evaluates the impact of various pedagogical models. The results consistently show that TGfU contributes to improved technical abilities, game comprehension, and student enthusiasm. Moreover, integrating TGfU with unstructured practice or SE produces greater gains in performance and involvement compared to using each method in isolation. These findings provide practical guidance for educators and curriculum designers aiming to enhance basketball teaching through interactive, student-centered learning frameworks